Preventive Effect of Alpha-pinene on Cisplatin-induced Kidney Injury by Oxidative Stress, Inflammation and Apoptosis via NF-ΚB Signaling Pathway - Tan, Junhua (Letters in Drug Design & Discovery, 2024)
Introduction: The chemotherapy medication cisplatin is highly effective and is used in treating a wide variety of cancers. Tumor resistance and dose-related severe side effects, including kidney and hearing damage and suppressed bone marrow function, limit its clinical utility. This study aimed to investigate the nephroprotective effect of alpha-pinene against cisplatin-induced nephrotoxicity in male albino Wistar rats. Methods: A total of 24 rats were divided into four groups containing six animals. Alpha-pinene (50 mg/kg) was administered orally for 14 days, and cisplatin (50 mg/kg) was given intraperitoneally for the last two consecutive days (13th and 14th day). Kidney function markers, lipid peroxidative markers, antioxidant status, inflammatory markers, and apoptotic gene expressions were analyzed. The cisplatininduced rats significantly elevated kidney function markers, inflammatory markers, and pro-apoptotic genes in kidney tissues. Further, the antioxidant level/activities and antiapoptotic gene expression were significantly diminished in cisplatin-induced rats. Results: Pretreatment with alpha-pinene significantly decreased kidney function markers, inflammatory markers, and pro-apoptotic genes and increased antioxidant status and antiapoptotic genes. Conclusion: These findings provide the protective effect of alpha-pinene against CP-induced nephrotoxicity, as measured by potent antioxidant and antiapoptotic properties.
Keywords: Alpha-pinene